Optimal Diagnostic Indices for Idiopathic Normal Pressure Hydrocephalus Based on the 3D Quantitative Volumetric Analysis for the Cerebral Ventricle and Subarachnoid Space - Yamada, S.; Ishikawa, M.; Yamamoto, K. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Despite the remarkable progress of 3D graphics technology, the Evans index has been the most popular index for ventricular enlargement. We investigated a novel reliable index for the MR imaging features specified in idiopathic normal pressure hydrocephalus, rather than the Evans index.MATERIALS AND METHODS: The patients with suspected idiopathic normal pressure hydrocephalus on the basis of the ventriculomegaly and a triad of symptoms underwent the CSF tap test. CSF volumes were extracted from a T2-weighted 3D spin-echo sequence named “sampling perfection with application-optimized contrasts by using different flip angle evolutions (SPACE)” on 3T MR imaging and were quantified semiautomatically. Subarachnoid spaces were divided as follows: upper and lower parts and 4 compartments of frontal convexity, parietal convexity, Sylvian fissure and basal cistern, and posterior fossa. The maximum length of 3 axial directions in the bilateral ventricles and their frontal horns was measured. The “z-Evans Index” was defined as the maximum z-axial length of the frontal horns to the maximum cranial z-axial length. These parameters were evaluated for the predictive accuracy for the tap-positive groups compared with the tap-negative groups and age-adjusted odds ratios at the optimal thresholds.RESULTS: In this study, 24 patients with tap-positive idiopathic normal pressure hydrocephalus, 25 patients without response to the tap test, and 23 age-matched controls were included. The frontal horns of the bilateral ventricles were expanded, with the most excessive expansion being toward the z-direction. The CSF volume of the parietal convexity had the highest area under the receiver operating characteristic curve (0.768), the z-Evans Index was the second (0.758), and the upper-to-lower subarachnoid space ratio index was the third (0.723), to discriminate the tap-test response.CONCLUSIONS: The CSF volume of the parietal convexity of <38 mL, upper-to-lower subarachnoid space ratio of <0.33, and the z-Evans Index of >0.42 were newly proposed useful indices for the idiopathic normal pressure hydrocephalus diagnosis, an alternative to the Evans Index.AUCarea under the receiver operating characteristic curveDESHdisproportionately enlarged subarachnoid spaceiNPHidiopathic normal pressure hydrocephalusSPACEsampling perfection with application-optimized contrasts by using different flip angle evolutions